Effect of sunflower oil supplementation in feed on body weight and hematobiochemical parameters in mice (Progressive Agriculture, 2017)
Sunflower oil contain high concentrations of essential polyunsaturated fat with antioxidant vitamin E. The study was carried out on Swiss Albino healthy mice to evaluate the effects of additional supplementation of sunflower oil in feed on body weight, hematological parameters (total erythrocyte count and hemoglobin concentration) and biochemical parameters (total serum cholesterol, triglycerides, high density lipoproteins, low density lipoprotein and serum creatine). A total of 20, three-weeks old mice were randomly divided into two equal groups ( n=10) as A and B. Group A was considered as control (standard poultry pellet) and group B was supplemented with sunflower oil (5 mL/kg feed) respectively in addition to standard poultry pellet for 50 days. At the end of experimental trial, the mice were sacrificed for analysis of hemato-biochemical parameters. Body weight was significantly (P